Literature and drama : with special reference to Shakespeare and his contemporaries - Wells, Stanley, 1930- (Routledge library editions. Shakespeare. Critical studies, 2005)
First published in 1970. This book examines the areas of plays that are dependent upon the art of the theatre and the fluidity of interpretation to which this gives rise. It discusses the printing of plays and the limited attempts that have have been made to convey theatrical experience, taking as a particular example a masque by Ben Jonson. Finally, some of the problems created by the instability of theatrical art.